Protestant and Irish : the minority's search for a place in independent Ireland - Milne, Ida; D'Alton, Ian (Book collections on Project MUSE., 2019)
Even before the end of the union with Britain, southern Irish unionists were being represented as stateless, rootless. Popular opinion has often erroneously conflated 26 county Protestantism with 26 county Unionism, but the two are not synonymous. This book of essays aims to show both that, and how Irish Protestants went about finding a place in in the new Ireland. From various perspectives of Protestant participants in the new Ireland -- such as academics and students, working class Protestants, revolutionaries, rural women, a landlord, clerics, -- it examines how they accommodated themselves to the changed dispensation. In our view, our volume will stand complementary to the works cited (and others, such Kurt Bowen's sociological work, Protestants in a Catholic state: Ireland's privileged minority (McGill, 1983) and M. Macourt, Counting the people of God? The Census of Population and the Church of Ireland (Dublin, 2008) on Church of Ireland historical demography). We hope that this volume will enable readers to draw broader and deeper conclusions about the nature of Protestant attitudes and adjustment to the new regime after 1922 than has hitherto been the case.